Effect of gender on mathematics achievement in Class Eight at Khotang District - Chhetri, Padam Bahadur Bista (DMC Journal, 2022)
This study was undertaken to assess gender differences in mathematics achievement. Data was collected by questionnaire, interview schedules and class examination administered previously on 2075. The accessible population was teachers of mathematics, class eight students from selected secondary schools in Diktel Rupakot Majhuwagadhi Municipality in Khotang District and their Parents. Two community school and one institutional school were selected by purposively. 18 boys and 18 girls’ progress report were selected from each school six boys and six girls by random sampling. six parent two from each school representing one boy and one girl were selected purposively. Three mathematics teachers were selected. Data were collected from teacher and parents by questionnaire and interview schedules. It is found that there is gender difference in mathematics achievement in class eight. Specially, boys’ achievement in mathematics is better than girls’ achievement in mathematics. It is also found that causes of comparatively poorer achievement of girls are rapid physical growth, over responsibility at home and at school.